2020
DOI: 10.1016/j.gca.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of calcite solubility and the stability of aqueous Ca– and Na–carbonate and –bicarbonate complexes at 100–160 °C and 1–50 bar pCO2 using in situ pH measurements

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…At 25 °C, the retrograde solubility of calcite, K SP‑cal , is 10 –8.48 , for the reaction Ca­(CO 3 ) ⇌ Ca 2+ + CO 3 2– , and decreases to ca. 10 –11.5 at 205 °C . For our synthetic multi-REE polymorphs, we will use kozoite-(Nd) and hydroxylbastnäsite-(Nd) as thermodynamic proxies (see the rationale in SI Text S3).…”
Section: Resultsmentioning
confidence: 99%
“…At 25 °C, the retrograde solubility of calcite, K SP‑cal , is 10 –8.48 , for the reaction Ca­(CO 3 ) ⇌ Ca 2+ + CO 3 2– , and decreases to ca. 10 –11.5 at 205 °C . For our synthetic multi-REE polymorphs, we will use kozoite-(Nd) and hydroxylbastnäsite-(Nd) as thermodynamic proxies (see the rationale in SI Text S3).…”
Section: Resultsmentioning
confidence: 99%
“…In-line pH sensors, designed for continuous data measurement, have been used in the biotech and pharmaceutical industries for a number of years [48][49][50]. However, there are a limited number of electrode systems capable of providing in-situ pH measurements at temperatures greater than 100 • C and at pressures greater than saturated water pressure.…”
Section: Industrial Applications Of In-line Ph Measurement Under Chal...mentioning
confidence: 99%
“…Beginning with Engel in 1889, many researchers have studied the solubility of calcite under different conditions [31,32]. The pK sp (298.15 K) values of calcite are reported to be around 8.40 [33,34].The saturated solution compositions of fluorite and calcite are shown in Figure 2 [35].…”
Section: Solubilitymentioning
confidence: 99%
“…Beginning with Engel in 1889, many researchers have studied the solubility of calcite under different conditions [31,32]. The pKsp (298.15 K) values of calcite are reported to be around 8.40 [33,34].The saturated solution compositions of fluorite and calcite are shown in Figure 2 As illustrated in the diagrams, the main components of fluorite within the pH8-10 (conventional fluorite flotation pH range) are Ca 2+ and F − , and the main components of calcite are Ca 2+ , CO3 2− and HCO3 − .The results of solution chemistry calculations and XPS spectral analysis in several previous studies [36,37] showed that the dissolved F − and CO3 2− can adsorb on the surface of calcite and fluorite, respectively and form the corresponding calcium-containing compounds, which homogenizes the chemical properties of fluorite and calcite surfaces.…”
Section: Peer Reviewmentioning
confidence: 99%